Land observation by remote sensing (Gordon and Breach Science Publishers, 1993)
This volume is an updated and internationalised English language version of the successful Dutch text. Land Observation by Remote Sensing: Theory and Applications focuses on earth-surface objects and describes both the theory of remote sensing and the applications of irrigation, nature conservation and environmental pollution control. Its purpose is to provide a systematically structured survey of the theory behind the applications described, and also covers the fundamentals of electromagnetic waves and sensor instrumentation formulated at university level. The textbook is divided into nine topics with special consideration given to the ''object'' approach, leaving the ''sensor'' approach in the background, though the historical gap that exists between these concepts in the respective fields of the optical and microwave wavelength regions is bridged.